Evaluating the Relation of Cave Passage Formation to Stress-Field: Spatio-Temporal Correlation of Speleogenesis with Active Tectonics in Asprorema Cave (Mt. Pinovo, Greece) - Georgios Lazaridis; Emmanouil Katrivanos; Despoina Dora; Lambrini Papadopoulou; Ilias Lazos; Alexandros Chatzipetros (Geosciences, 2024)
Caves serve as time capsules, preserving significant markers of tectonic activity and offering insights into geological history. Fault geometries and past activations found in caves can be correlated with known deformational events in the broader area, temporally delimiting the speleogenesis. More specifically, cave passage formation is suggested to be affected by the regional stress-field. The Asprorema Cave in Northern Greece is a typical example of a fracture guided cave, with passage geometry influenced by relative sidewall movements, revealing these discontinuities as faults. This study constructs the timeframe and conceptual model of speleogenesis in relation to tectonic events, geomorphological evolution and hydrological zones, and verifies its relation to the stress-field. Active tectonics, mineralogy and cave geomorphology are investigated. Results suggest syntectonic speleogenesis under phreatic and epiphreatic conditions. The absence of corrosion on fault slip surfaces implies recent activations post cave’s shift to the vadose zone. Structural analysis identifies three main neotectonic phases: NNW-SSE striking faults (oldest group of structures), NE-SW striking faults with dextral strike-slip movement (post-middle Miocene), and NE-SW striking normal faults indicating extensional stress-regime (Quartenary). The last two phases affect cave passage shape causing wall displacement, highlighting passage formation along discontinuities perpendicular to the horizontal minimum stress axis.